2016
DOI: 10.2217/imt-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PD-L1 for Non-Small-Cell Lung Cancer

Abstract: Lung cancer is the leading cause of cancer-related death worldwide. For decades, cytotoxic chemotherapy has been the mainstay of treatment for the majority of patients, yet median survival remains poor and side effects from chemotherapy are not trivial. Immune checkpoint inhibitors, which exert antitumor effects by inhibiting negative T-cell regulators, are changing the landscape of treatment options for patients with non-small-cell lung cancer (NSCLC). The anti-PD-1 antibodies nivolumab and pembrolizumab are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…A series of immunotherapeutic approaches, including anti-PD-1 therapy and anti-PD-L1 therapy, had previously been established for NSCLC (7,32). In this study, our results showed that SIRPaD1-Fc therapy could elicit potent anti-NSCLC efficacy in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 58%
“…A series of immunotherapeutic approaches, including anti-PD-1 therapy and anti-PD-L1 therapy, had previously been established for NSCLC (7,32). In this study, our results showed that SIRPaD1-Fc therapy could elicit potent anti-NSCLC efficacy in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 58%
“…PD-L1 expression was also detected on the cell surfaces of numerous types of cancer, including bladder, kidney, ovarian, lung, and melanoma, which was associated with poorer immune response and worse prognosis for patients. The large amounts of PD-L1 help some cancer cells to hide from an immune attack (Feld et al, 2016;Lee et al, 2016;Maleki et al, 2017;Xiang et al, 2017;Rom-Jurek et al, 2018). The presence of this protein has been also demonstrated in colorectal carcinoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer, one of the most frequently diagnosed cancers, has become the leading cause of cancer‐related death worldwide . According to Global Cancer Statistics 2018, lung cancer is responsible for approximately 2.09 million newly diagnosed cancer cases and 1.76 million cancer‐related deaths worldwide .…”
Section: Introductionmentioning
confidence: 99%
“…During the past two decades, some advancements in the treatments of NSCLC have been achieved, such as the application of small molecule tyrosine kinase inhibitors and immunotherapy, which benefit to some selected patients . Nevertheless, the prognosis of NSCLC patients (especially those with metastasis disease) is still dismal, with a 5‐year survival rate of just 15% . Hence, continued research into more effective screening for predicting disease progression in NSCLC patients at an early stage is required, and with this aim, molecular markers may expand the screening approach to improve prognosis in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation